2010
DOI: 10.3178/hrl.4.20
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of Regional-Mean Probable Precipitation by High-Resolution Climate Models

Abstract: Abstract:We assessed the reproducibility of regional-mean probable precipitation in Japan estimated based on the results of three runs of a 20km-mesh global climate model (MRI-GCM20) and one run of a 20km-mesh regional climate model (MRI-RCM20). These models inappropriately simulate the annual maximum daily precipitation at individual grid points, especially in relation to the spatial pattern, but estimate the regional mean reasonably well. MRI-GCM20 runs simulated data over annual maximum regional-mean 10-day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…However, a super-high-resolution atmospheric general circulation model with a horizontal grid size of about 20 km (MRI-GCM20) has already been developed by MRI as part of the KAKUSHIN Program, and the projection results have been used in various assessments (e.g., Mizuta et al, 2006;Kitajima et al, 2010;Kitoh et al, 2009). Furthermore, research groups have been developing high-resolution climate models able to reproduce the present-day local climate in areas of Japan characterized by complex mountainous terrain (e.g., Ishizaki and Takayabu, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a super-high-resolution atmospheric general circulation model with a horizontal grid size of about 20 km (MRI-GCM20) has already been developed by MRI as part of the KAKUSHIN Program, and the projection results have been used in various assessments (e.g., Mizuta et al, 2006;Kitajima et al, 2010;Kitoh et al, 2009). Furthermore, research groups have been developing high-resolution climate models able to reproduce the present-day local climate in areas of Japan characterized by complex mountainous terrain (e.g., Ishizaki and Takayabu, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the smallest scale of weather events able to be represented by climate models is generally several times the horizontal resolution of the model. Considering these limitations, regional assessments of future change might be more appropriate than "at-site" analyses (Ishihara, 2010b;Kitajima et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of smaller topography in models with 20-km resolution allows simulation of realistic precipitation patterns in Japan (Mizuta et al 2006). However, those models still represent regional precipitation averages better than point estimates (Kitajima et al 2010). Despite the model bias of not representing extreme rainfall well, Mizuta et al (2005) found that precipitation indices should increase, especially in western Japan and Hokkaido, and that the changes in other areas were insignificant.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al (2010) evaluated hydrologic discharge on the controlled simulation output of MRI-GCM20 using observed river discharge data and introduced that MRI-GCM20 provides relevant discharge output when the basin scale is more than 5000 km 2 . Kitajima et al (2010) investigated the reproducibility of regional-mean probable precipitation in Japan estimated based on the results of MRI-GCM20 and MRI-RCM20. They showed that the reproducibility of the average and standard deviation of the annual maximum precipitation is correlated with that of 30-year return values.…”
Section: Introductionmentioning
confidence: 99%